Influence of Financing Infrastructure on Implementation of Health Care Projects in Meru County, Kenya - Dr. Keiyoro Peter Njenga, Gitonga Zaberio, (International Journal of Scientific Research and Management (IJSRM), 2017)
Devolution of the healthcare function from the national government in Kenya to county governments is influenced by various socio-economic and political factors. In particular, the provision of health infrastructure for healthcare under the management of county governments presents various challenges to these devolved units of governance. This study investigated the influence of financing of health infrastructure on implementation of healthcare projects in Meru County. The study is hinged on one theory; Theory of Fiscal Decentralization. The study adopted Descriptive survey research design. Target population was composed of 703 respondents; 23 Department of Health Non-medical staff, 670 Medical Personnel and 10 Health Civil Society Organizations’ Managers. For this study, a sample size of 249 participants was used and subjects selected making uses of Stratified and Simple random sampling. Two questionnaires were used to collect primary data from the sampled respondents. Quantitative data was analyzed through the application of descriptive statistics while qualitative data was outlined in narratives modeled on themes under research. The study established that funding disbursed from central governments, budgetary constraints and revenue through local all influenced the financing of health infrastructure. The study concluded that adequate financial resources disbursed in good time are key drivers of the financing of health infrastructure that influenced the implementation of healthcare projects by in Meru County. The study recommends that, The Ministry of Health should advocate that the Ministry of Finance should devolve more financial resources for the purchase and implementation of health infrastructure at county government levels for implementation of healthcare projects.